Efeito da privação da glutamina sobre as células secretoras do epitélio intestinal em um modelo in vitro de enteroide - Costa, Tie Bezerra (2012)
The intestinal epithelium is formed and sustained by a population of stem cells capable of generating different cell lines while maintaining pluripotent and self-renewal capacity. Glutamine is a conditional essential amino acid important for the maintenance of the intestinal epithelium. However, few studies to date have explored the role of glutamine in the fine regulation of the intestinal crypt cell turnover. In order to evaluate the role of glutamine in the crypt cell turnover, an in vitro enteroid model was used, where stem cells are capable of generating an epithelium containing the main intestinal secretory cell lines (Paneth, goblet, and enteroendocrine cells) and absorptive enterocytes as well, while forming a villus-crypt like structure. This model was used to test the effect of 24h of glutamine deprivation (standard media with 2mM glutamine vs glutamine-free media) on epithelial turnover by counting EdU- labeled cells/total number per section and cell apoptosis by counting cleavage-caspase 3- labeled cells/total number per section. In order to assess crypt secretory function, Paneth and goblet crypt cell ratios (target secretory cell/total cell number per crypt) were measured. The number of Paneth and goblet cells was measured with the aid of confocal microscopy and lysozyme and mucin-2 immunostainning. In addition, Paneth and globet cell product transcripts (lysozyme and mucin, respectively) were measured using quantitative Real-time PCR. In order to assess the potential immunomodulatory role of glutamine, innate immune element transcripts, Toll like receptor and their accessory protein MD-2, and cytokines, as follows: TNF-α, IL-1β and CXCL-1, were measured. Glutamine deprivation reduced the number of EdU positive cell ratio as compared with the enteroid under the standard media (p=0.006). No significant differences regarding Paneth and goblet cell ratios were seen between groups following glutamine deprivation. Glutamine deprivation significantly decreased lysozyme transcripts as compared with the enteroid under the standard media (p=0.007), but not for mucin-2 transcripts, related to goblet cell function. Decreased TNF-α and MD-2 transcription (p=0.005 and p=0.016, respectively) were found following glutamine deprivation. Altogether, our findings reinforce the glutamine positive role on the intestinal epithelial turnover and furthermore suggest an important glutamine regulatory effect over Paneth cells and the innate immune system. The enteroid model provides an important tool the dissect the mechanisms of glutamine protection and shed light for future studies.